1998
DOI: 10.1063/1.121764
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Si+ implant activation efficiency in GaN using a high-temperature rapid thermal process system

Abstract: Si + implant activation efficiencies above 90%, even at doses of 5×1015 cm−2, have been achieved in GaN by rapid thermal processing at 1400–1500 °C for 10 s. The annealing system utilizes molybdenum intermetallic heating elements capable of operation up to 1900 °C, producing high heating and cooling rates (up to 100 °C s−1). Unencapsulated GaN shows severe surface pitting at 1300 °C and complete loss of the film by evaporation at 1400 °C. Dissociation of nitrogen from the surface is found to occur with an appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 21 publications
1
22
1
Order By: Relevance
“…We have found that Si, the most common n-type dopant, shows no detectable redistribution at 1400 °C, and that annealing at this temperature produces activation percentages of ≥90% [19,20]. Annealing at 1500 °C led to a reduction in both sheet electron concentration and electron mobility, which is consistent with self-compensation through site-switching of the Si.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…We have found that Si, the most common n-type dopant, shows no detectable redistribution at 1400 °C, and that annealing at this temperature produces activation percentages of ≥90% [19,20]. Annealing at 1500 °C led to a reduction in both sheet electron concentration and electron mobility, which is consistent with self-compensation through site-switching of the Si.…”
Section: Introductionsupporting
confidence: 63%
“…13 cm -2 , corresponds to a peak volume density of ~5×10 18 cm -3 . This is well below that achieved with Si + implantation and annealing (>10 20 cm -3 ) [17,20]. In the latter case the carrier density showed an activation energy of 5.2 eV.…”
Section: Results and Discussion (A) Residual Damagementioning
confidence: 87%
“…However, to bring the crossover frequency near the optical range, a doping level of at least 3 ¢ 10 20 cm 3 is required. The necessity of doping semiconductors so heavily raises concerns about the solid solubility limit, the fraction of dopants that would be active, and doping compensation effects [116,117]. Another major concern at such high doping levels is retaining the high carrier mobility that is essential for low losses.…”
Section: Semiconductorsmentioning
confidence: 99%
“…However, some localized failures of the AlN caps are observed; several groups have reported pitted surfaces in Siimplanted AlN capped GaN after annealing at temperatures higher than or equal to 1300°C. 3,[7][8][9] The structure of these pits and the mechanism that leads to their formation has not been fully explained. In this letter, we present the microscopic study of the failure mechanisms of such caps in relation to the protection that they provide during high temperature annealing of RE implanted GaN epilayers providing clear indications for producing caps with a higher resistance to degradation.…”
mentioning
confidence: 99%
“…7-9͒, had thicknesses of 50 or 120 nm, much larger than those used in our study. Cao et al 9 discussed the possible influence of residual H 2 bubbles in the AlN layer as a source of occasional localized cap fractures. Zolper et al 4 suggested that the AlN cap on Si-implanted GaN might fail due to poorly defined stoichiometry, or the evolution of hydrogen from the GaN that could break the AlN during escape.…”
mentioning
confidence: 99%